Inducing microscopic thermal lesions for the dissection of functional cell networks on a chip. Issue 1 (30th October 2014) - Rinklin, Philipp; Afanasenkau, Dzmitry; Wiegand, Simone; Offenhäusser, Andreas; Wolfrum, Bernhard
Abstract : Electrical heating of microstructured conductors is used to induce highly resolved lesions in confluent layers of cardiomyocytes. Abstract : We present a versatile chip-based method to inflict microscopic lesions on cellular networks or tissue models. Our approach relies on resistive heating of microstructured conductors to impose highly localized thermal stress on specific regions of a cell network. We show that networks can be precisely dissected into individual subnetworks using a microwire crossbar array. To this end, we pattern a network of actively beating cardiomyocyte-like cells into smaller subunits by inflicting thermal damage along selected wires of the array. We then investigate the activity and functional connectivity of the individual subnetworks using a Ca 2+ imaging-based signal propagation analysis. Our results demonstrate the efficient separation of functional activity between individual subnetworks on a microscopic level. We believe that the presented technique may become a powerful tool for investigating lesion and regeneration models in cellular networks.